Spectroscopy of CASSOWARY gravitationally lensed galaxies in SDSS: characterization of an extremely bright reionization-era analogue at z = 1.42. Issue 3 (8th February 2023) - Mainali, Ramesh; Stark, Daniel P; Jones, Tucker; Ellis, Richard S; Hezaveh, Yashar D; Rigby, Jane R
ABSTRACT: We present new observations of 16 bright ( r = 19–21) gravitationally lensed galaxies at z ≃ 1–3 selected from the CASSOWARY survey. Included in our sample is the z = 1.42 galaxy CSWA-141, one of the brightest known reionization-era analogues at high redshift (g = 20.5), with a large specific star formation rate (31.2 Gyr −1 ) and an [O iii ]+H  β equivalent width (EW[O iii ] + H β = 730 Å) that is nearly identical to the average value expected at z ≃ 7–8. In this paper, we investigate the rest-frame UV nebular line emission in our sample with the goal of understanding the factors that regulate strong C iii ] emission. Although most of the sources in our sample show weak UV line emission, we find elevated C iii ] in the spectrum of CSWA-141 (EWC iii ] = 4.6 ± 1.9 Å) together with detections of other prominent emission lines (O iii ], Si iii ], Fe ii ⋆, Mg ii ). We compare the rest-optical line properties of high-redshift galaxies with strong and weak C iii ] emission, and find that systems with the strongest UV line emission tend to have young stellar populations and nebular gas that is moderately metal-poor and highly ionized, consistent with trends seen at low and high redshift. The brightness of CSWA-141 enables detailed investigation of the extreme emission line galaxies which become common at z > 6. We find that gas traced by the C iii ] doublet likely probes higher densities than that traced by [O ii ] and [S ii ]. Characterization of the spectrally resolved Mg ii emission line and several low-ionization absorption lines suggests neutral gas around the young stars is likely optically thin, potentially facilitating the escape of ionizing radiation.